PERAN PEMERINTAHAN DESA TERHADAP PEMBANGUNAN PEREKONOMIAN MELALUI BADAN USAHA MILIK DESA (BUMDes) MITRA USAHA MULYA DI DESA MARGA MULYA KECAMATAN RAMBAH SAMO KABUPATEN ROKAN HULU TAHUN 2014 – 2015 - Lestari, Titin; Amin, Raja Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
In the village of Marga Mulya District of Rokan Hulu Rambah Samo doing rural development through several activities, such as improving the environment and housing, development of rural economic enterprises, the development of rural financial institutions, as well as activities that can improve the ability of communities to increase their production. Pemerdayaan community is an starategi committed to independence by the socio-economic in the long run. The role of village government should be able to perform tasks empower rural communities. To get the data and information depth interviews to the village and villagers. Informants were selected based sampling nonprobabilitiy by purposive sampling that only people who are experts and understand the phenomena that occur. The results showed that the role of Village Government's role in economic development through BUMDes very dominant in the formation and development BUMDes, Village Government be responsible for any positions each - each. Factors that become an obstacle in pursuing Economic Development Rural Marga Mulya through BUMDes in Rokan Hulu namely: Structuring village institutions has not run optimally so BUMDes is not yet institutionalized in the form of governance and rural economies, limited capacity of human resources in villages to manage and BUMDes develop accountable and well-performing, low local initiatives to drive local economic potential for the improvement of social and economic welfare of the villagers and the village government's lack of responsiveness to make BUMDes as a flagship program to empower rural and community welfare.Keywords: Village Governance, Economic Development, BUMDes